"Seeing to Make Disappear": The Lingering Ghost of Slavery and Stereotypical Representations of Blackness in Brazilian Telenovelas of the Last Decades of the Twentieth Century. - Berktay, Asligul (Luso-Brazilian Review, 2023)
This article explores the representations of Black Brazilians in telenovelas where the ideology of racial democracy remains evident through the act of "seeing to make disappear"—a complicated process of mutual exclusion and incorporation. Rather than a microcosm per se, telenovelas form integral parts of the contemporary Brazilian cosmology, primary tenets of a "worldview" which Brazilians have of their "imagined community." The precepts of modernity and racial democracy are key to the construction of this "televisual cosmology." I also place representations of Blackness within historical discussions on Brazilian slavery, as it is impossible to speak about race and race relations in the Atlantic world without going back to the historical roots of its respective slave societies. The invisibility and relegation of Black individuals to flat characters, their stereotypical representations, and the mechanisms of "completion" and "distancing" remain central to the telenovelas of the last decades of the twentieth century. Este artigo explora a representação de brasileiros negros em novelas em que a ideologia da democracia racial continua a existir através do ato de "ver para fazer desaparecer"—um processo complexo de exclusão e integração simultâneas. Mais do que um microcosmo em si, as novelas constituem parte integrante da cosmologia brasileira contemporânea, incorporando conceitos básicos à visão que os brasileiros têm de sua "comunidade imaginada." Os princípios de modernidade e democracia racial são essenciais para a construção dessa "cosmologia televisual." O artigo também situa as representações da negritude no contexto das discussões históricas sobre escravidão no Brasil, posto que é impossível falar de raça e de relações raciais no Mundo Atlântico sem voltar às raízes das suas sociedades escravistas. A invisibilidade dos negros, relegados a personagens unidimensionais, sua representação por estereótipos e os mecanismos de "preenchimento" e "distanciamento" permanecem centrais nas novelas das últimas décadas do século XX.